Preparation method of diaphragm-free all-solid-state battery
By coating the surface of the positive electrode sheet of the solid-state battery with lithium niobate and porous carbon coated alumina particles, forming an acting layer and a semi-solid electrolyte, the problem of concentrating lithium ions at the interface is solved and the cycle life of the solid-state battery is significantly improved.
Patent Information
- Application Number
- CN202411837099.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
In solid-state batteries, the concentration of lithium ions at the interface leads to excessive local current density, local overheating, intensified dendrites' growth or interface failure, affecting the cycle life of the battery.
The preparation method of a separator-free all-solid state battery is adopted. By coating the active slurry and the electrolyte slurry on the surface of the positive electrode sheet, an action layer and a semi-solid electrolyte are formed. The active slurry contains 15-18% lithium niobate, and the electrolyte slurry contains porous carbon coated alumina particles.
The cycle life of the battery is synergistically improved, allowing the battery to charge at 0.5C/discharge until the capacity retention rate is reduced to 80% to more than 1691 cycles.
Smart Images

Figure CN119674254A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a method for preparing a diaphragm-free all-solid-state battery. Background Art
[0002] The traditional liquid lithium battery is also vividly called a "rocking chair battery" by scientists. The two ends of the rocking chair are the positive and negative poles of the battery, and the electrolyte (liquid) is in the middle. Lithium ions are like excellent athletes, running back and forth between the two ends of the rocking chair. In the process of lithium ions moving from the positive electrode to the negative electrode and then to the positive electrode, the battery's charging and discharging process is completed. The principle of solid-state batteries is the same, except that its electrolyte is solid, and its density and structure allow more charged ions to gather at one end, conduct greater current, and thus increase the battery capacity. Therefore, with the same amount of electricity, the volume of solid-state batteries will become smaller.
[0003] In solid-state batteries, the solid-solid interface between the solid electrolyte and the electrode material is one of the key factors affecting battery performance. Studies have shown that during the solidification process of the solid electrolyte, lithium ions will concentrate on the surface, which plays an important role in improving the interface stability and conductivity of the battery. When lithium ions are enriched at the interface, a stable lithium ion conductive layer can be formed, which helps to reduce the interface resistance and improve the charge and discharge efficiency of the battery.
[0004] However, this concentration effect can lead to problems such as excessive local current density, local overheating, increased dendrite growth or interface failure, affecting the cycle life of the battery. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a method for preparing a diaphragm-free all-solid-state battery, which can improve the cycle life of the prepared diaphragm-free all-solid-state battery.
[0006] In order to achieve the above object, the present invention provides a method for preparing a diaphragm-free all-solid-state battery, comprising the following steps:
[0007] S1. The positive current collector surface is coated with positive electrode slurry, with a surface loading of 25-30 mg / cm 2 , bake to a semi-dry state to obtain a positive electrode sheet;
[0008] S2, positive electrode surface coating slurry, surface loading 4-5mg / cm 2 , baked to a semi-dry state to form an active layer; the components of the active slurry, by mass percentage, include 15-18% lithium niobate, 5-6% nano-aluminum oxide, 3-5% binder and the remainder solvent;
[0009] S3, the surface of the active layer is coated with electrolyte slurry, with a surface loading of 15-18 mg / cm 2, baked to a semi-dry state to form a semi-solid electrolyte; the components of the electrolyte slurry, measured by mass percentage, include 5-7% porous carbon-coated alumina particles, 7-9% binder and the remainder of electrolyte;
[0010] S4, the surface of the semi-solid electrolyte is coated with negative electrode slurry, with a surface loading of 25-30 mg / cm 2 Then, a negative current collector is placed on the surface and the surface is pressurized to a pressure of 450-650 N / m 2 , heat treatment at 80-100℃ in an oven in an inert environment for 12-15h to obtain a battery cell;
[0011] S5. Encapsulate, compact and seal the battery cell to obtain a diaphragm-free all-solid-state battery.
[0012] Further, in S3, the preparation method of the porous carbon-coated alumina particles is as follows:
[0013] A1. Disperse 1 part of nano-alumina in 10-15 parts of anhydrous ethanol by weight, add 0.02-0.04 parts of silane coupling agent, stir for 20-30 minutes, filter, and obtain activated alumina;
[0014] A2, mixing the activated alumina obtained in A1 with oleic acid in a mass ratio of 1:3, and then ball milling for 0.5-1.5 h, filtering, and obtaining modified alumina;
[0015] A3. Add modified alumina, fine-grained asphalt and graphite in a mass ratio of 5:1:1 into a high-speed mixer, stir for 2-3 hours, mix evenly, and obtain a mixture;
[0016] A4. Place the mixture in a tube furnace, and under nitrogen protection, heat it to 1000-1200°C at 3-5°C / min, keep it warm for 4-6 hours, and then naturally cool it to room temperature. Grind it, and pass it through a 500-mesh screen to obtain porous carbon-coated alumina particles.
[0017] Furthermore, in A1, the silane coupling agent is KH550.
[0018] Furthermore, in S3, the electrolyte is lithium manganese iron phosphate electrolyte KLD-LMFP03A.
[0019] Furthermore, in S1, the components of the positive electrode slurry include, by mass percentage, 45-50% lithium cobalt oxide, 4-5% binder, 2-3% carbon black and the remainder solvent.
[0020] Furthermore, in S4, the components of the negative electrode slurry include, by mass percentage, 35-40% silicon carbon, 4-5% binder, 2-3% carbon black and the remainder solvent.
[0021] Furthermore, the binder includes polyvinylidene fluoride and / or sodium carboxymethyl cellulose.
[0022] Furthermore, the solvent includes N-methylpyrrolidone and / or ethyl methyl carbonate.
[0023] Furthermore, the positive current collector is aluminum foil, and the negative current collector is copper foil.
[0024] This application has the following beneficial effects:
[0025] 1. In the preparation of the diaphragm-free all-solid-state battery of the present invention, an active slurry is coated on the surface of the positive electrode to form an active layer, and the active slurry contains 15-18% of lithium niobate; the surface of the active layer is coated with an electrolyte slurry to form a semi-solid electrolyte, and the electrolyte slurry contains porous carbon-coated alumina particles; when the active slurry contains 15-18% of lithium niobate, the porous carbon-coated alumina particles contained in the electrolyte slurry can produce a synergistic effect therewith, and synergistically improve the cycle life of the prepared battery, so that the number of cycles of the prepared battery at 0.5C charging / 0.5C discharging until the capacity retention rate is reduced to 80% is as high as more than 1691 times.
[0026] 2. The surface of the positive electrode is coated with an active slurry. The lithium niobate contained in the active slurry can effectively inhibit the chemical / electrochemical side reactions and interface creep at the positive electrode side interface. This interface modification layer can have a certain repulsive effect on lithium ions, thereby affecting their distribution and migration at the interface.
[0027] At the same time, the porous carbon-coated alumina particles contained in the electrolyte slurry, as a porous particle, not only have more surface area in contact with lithium ions, thereby increasing the adsorption and transmission opportunities of lithium ions, but also provide an effective diffusion channel for lithium ions, and shorten the diffusion distance of lithium ions, thereby improving the transmission efficiency of lithium ions, and then can produce a certain traction effect on lithium ions, affecting their distribution and migration. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 , a comparative trend chart of test data of the cycles of 0.5C charge / 0.5C discharge of batteries prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 6 until the capacity retention rate is reduced to 80%. DETAILED DESCRIPTION
[0029] The present application is further described in detail below with reference to the embodiments.
[0030] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0031] Example 1: (1) Preparation of porous carbon-coated alumina particles, the preparation method is as follows:
[0032] A1. Disperse 1 part of nano-alumina in 12 parts of anhydrous ethanol by weight, add 0.03 parts of KH550, stir at a stirring speed of 240 r / min for 25 minutes, filter, and obtain activated alumina.
[0033] A2. The activated alumina obtained in A1 was mixed with oleic acid in a mass ratio of 1:3 and ball-milled for 1 h. The mixture was filtered to obtain modified alumina.
[0034] A3. Add modified alumina, fine-grained asphalt and graphite in a mass ratio of 5:1:1 into a high-speed mixer, stir for 2.5 hours, mix evenly, and obtain a mixture.
[0035] A4. Place the mixture in a tube furnace, and under nitrogen protection, heat it to 1100°C at 4°C / min, keep it warm for 5 hours, then naturally cool it to room temperature, grind it, and pass it through a 500-mesh screen to obtain porous carbon-coated alumina particles.
[0036] Among them, nano-alumina (99.9%), 50nm grade, was purchased from Hangzhou Jiupeng New Materials Co., Ltd. Fine-grained asphalt (AC-10) was purchased from Shenzhen Huafa Asphalt Engineering Co., Ltd. Graphite is colloidal graphite (S-0), purchased from Qingdao Risheng Graphite Co., Ltd.
[0037] (2) A method for preparing a diaphragm-free all-solid-state battery, comprising the following steps:
[0038] S1, positive current collector surface coated with positive electrode slurry, surface loading 27.3mg / cm 2 , baked to a semi-dry state to obtain a positive electrode sheet. The positive current collector is aluminum foil. The components of the positive electrode slurry, by mass percentage, include 48% lithium cobalt oxide, 4.5% binder polyvinylidene fluoride, 2.5% carbon black and 45% solvent N-methylpyrrolidone.
[0039] Among them, lithium cobalt oxide (content 98%) was purchased from Henan Shuangjie Chemical Co., Ltd. Polyvinylidene fluoride (US Solvay 6008) was purchased from Shanghai Henghangmai Plastics Co., Ltd. Carbon black is conductive carbon black XC72 (CABOT), purchased from Tianjin Tianyi Century Chemical Products Technology Development Co., Ltd. N-methylpyrrolidone (content 99.9%) was purchased from Jinan Xinke Chemical Co., Ltd.
[0040] S2, positive electrode surface coating slurry, surface loading 4.5mg / cm 2 , baked to a semi-dry state to form an active layer; the components of the active slurry, calculated by mass percentage, include 16% lithium niobate, 5.5% nano-aluminum oxide, 4% binder polyvinylidene fluoride and 74.5% solvent N-methylpyrrolidone.
[0041] Among them, lithium niobate (99%, industrial grade) was purchased from Hubei Jusheng Technology Co., Ltd.
[0042] S3, the surface of the active layer is coated with electrolyte slurry, with a surface loading of 16.2 mg / cm 2 , baked to a semi-dry state to form a semi-solid electrolyte; the components of the electrolyte slurry, measured by mass percentage, include 6% porous carbon-coated alumina particles, 8% binder polyvinylidene fluoride and 86% electrolyte.
[0043] Among them, the electrolyte is lithium manganese iron phosphate electrolyte KLD-LMFP03A, which was purchased from Dongguan Kelode New Energy Technology Co., Ltd.
[0044] S4, the surface of the semi-solid electrolyte is coated with negative electrode slurry, with a surface loading of 26.8 mg / cm 2 Then, a negative current collector is placed on the surface and the surface is pressurized to a pressure of 550 N / m 2 , and heated in an oven at 90°C for 13 hours to obtain a battery cell. The components of the negative electrode slurry, by mass percentage, include 38% silicon carbon, 4.5% polyvinylidene fluoride as a binder, 2.5% carbon black, and 55% N-methylpyrrolidone as a solvent. The negative current collector is copper foil.
[0045] Among them, silicon carbon is purchased from Fujian Xinsen Carbon Industry Co., Ltd.
[0046] S5. The battery cell is encapsulated with an aluminum-plastic film, and the vacuum environment is used to exhaust, compact and seal the battery to obtain a diaphragm-free all-solid-state battery.
[0047] Example 2: The difference between this example and Example 1 is that: (1) porous carbon-coated alumina particles are prepared by the following method:
[0048] A1. Disperse 1 part of nano-alumina in 10 parts of anhydrous ethanol by weight, add 0.02 parts of KH550, stir at a stirring speed of 240 r / min for 20 minutes, filter, and obtain activated alumina.
[0049] A2. The activated alumina obtained in A1 was mixed with oleic acid in a mass ratio of 1:3 and ball-milled for 0.5 h. The mixture was filtered to obtain modified alumina.
[0050] A3. Add modified alumina, fine-grained asphalt and graphite in a mass ratio of 5:1:1 into a high-speed mixer, stir for 2 hours, mix evenly, and obtain a mixture.
[0051] A4. Place the mixture in a tube furnace, and under nitrogen protection, heat it to 1000°C at 3°C / min, keep it warm for 4 hours, then naturally cool it to room temperature, grind it, and pass it through a 500-mesh screen to obtain porous carbon-coated alumina particles.
[0052] Example 3: The difference between this example and Example 1 is that: (1) porous carbon-coated alumina particles are prepared by the following method:
[0053] A1. Disperse 1 part of nano-alumina in 15 parts of anhydrous ethanol by weight, add 0.04 parts of KH550, stir at a stirring speed of 240 r / min for 30 minutes, filter, and obtain activated alumina.
[0054] A2. The activated alumina obtained in A1 was mixed with oleic acid in a mass ratio of 1:3 and ball-milled for 1.5 h. The mixture was filtered to obtain modified alumina.
[0055] A3. Add modified alumina, fine-grained asphalt and graphite in a mass ratio of 5:1:1 into a high-speed mixer, stir for 3 hours, mix evenly, and obtain a mixture.
[0056] A4. Place the mixture in a tube furnace, and under nitrogen protection, heat it to 1200°C at 5°C / min, keep it warm for 6 hours, then naturally cool it to room temperature, grind it, and pass it through a 500-mesh screen to obtain porous carbon-coated alumina particles.
[0057] Example 4: The difference between this example and Example 1 is that: (2) A method for preparing a diaphragm-free all-solid-state battery comprises the following steps:
[0058] S1, positive current collector surface coated with positive electrode slurry, surface loading 25.3mg / cm 2 , baked to a semi-dry state to obtain a positive electrode sheet. The positive current collector is aluminum foil. The components of the positive electrode slurry, by mass percentage, include 45% lithium cobalt oxide, 4% binder polyvinylidene fluoride, 2% carbon black and 49% solvent N-methylpyrrolidone.
[0059] S2, positive electrode surface coating slurry, surface loading 4.1mg / cm 2 , baked to a semi-dry state to form an active layer; the components of the active slurry, calculated by mass percentage, include 15% lithium niobate, 5% nano-aluminum oxide, 3% binder polyvinylidene fluoride and 77% solvent N-methylpyrrolidone.
[0060] S3, the surface of the active layer is coated with electrolyte slurry, with a surface loading of 15.5 mg / cm 2 , baked to a semi-dry state to form a semi-solid electrolyte; the components of the electrolyte slurry, by mass percentage, include 5% porous carbon-coated alumina particles, 7% binder polyvinylidene fluoride and 88% electrolyte. The electrolyte is lithium manganese iron phosphate electrolyte KLD-LMFP03A.
[0061] S4, negative electrode slurry coated on the surface of semi-solid electrolyte, surface loading 25.9mg / cm 2Then, a negative current collector is placed on the surface and the surface is pressurized to a pressure of 450 N / m 2 , and heated in an oven at 80°C for 15 hours to obtain a battery cell. The components of the negative electrode slurry, by mass percentage, include 35% silicon carbon, 4% polyvinylidene fluoride as a binder, 2% carbon black, and 59% N-methylpyrrolidone as a solvent. The negative current collector is copper foil.
[0062] S5. Encapsulate, compact and seal the battery cell to obtain a diaphragm-free all-solid-state battery.
[0063] Example 5: The difference between this example and Example 1 is that: (2) A method for preparing a diaphragm-free all-solid-state battery comprises the following steps:
[0064] S1, positive current collector surface coated with positive electrode slurry, surface loading 29.4mg / cm 2 , baked to a semi-dry state to obtain a positive electrode sheet. The positive current collector is aluminum foil. The components of the positive electrode slurry, by mass percentage, include 50% lithium cobalt oxide, 5% binder polyvinylidene fluoride, 3% carbon black and 42% solvent N-methylpyrrolidone.
[0065] S2, positive electrode surface coating slurry, surface loading 4.7mg / cm 2 , baked to a semi-dry state to form an active layer; the components of the active slurry, calculated by mass percentage, include 18% lithium niobate, 6% nano-aluminum oxide, 5% binder polyvinylidene fluoride and 71% solvent N-methylpyrrolidone.
[0066] S3, the surface of the active layer is coated with electrolyte slurry, with a surface loading of 17.2 mg / cm 2 , baked to a semi-dry state to form a semi-solid electrolyte; the components of the electrolyte slurry, by mass percentage, include 7% porous carbon-coated alumina particles, 9% binder polyvinylidene fluoride and 84% electrolyte. The electrolyte is lithium manganese iron phosphate electrolyte KLD-LMFP03A.
[0067] S4, the surface of the semi-solid electrolyte is coated with negative electrode slurry, with a surface loading of 29.7 mg / cm 2 Then, a negative current collector is placed on the surface and the surface is pressurized to a pressure of 650 N / m 2 , and heated at 100°C in an inert environment of an oven for 12 hours to obtain a battery cell. The components of the negative electrode slurry, by mass percentage, include 40% silicon carbon, 5% polyvinylidene fluoride as a binder, 3% carbon black, and 52% N-methylpyrrolidone as a solvent. The negative current collector is copper foil.
[0068] S5. Encapsulate, compact and seal the battery cell to obtain a diaphragm-free all-solid-state battery.
[0069] Comparative Example 1: The difference between this comparative example and Example 1 is that in the working slurry, lithium niobate is replaced by nano-alumina; and in the electrolyte slurry, the porous carbon-coated alumina particles are replaced by a mixture of nano-alumina and graphite, and the mass ratio of nano-alumina to graphite is 5:2.
[0070] Specifically, the components of the active slurry, by mass percentage, include 21.5% of nano-alumina, 4% of binder polyvinylidene fluoride, and 74.5% of solvent N-methylpyrrolidone.
[0071] The components of the electrolyte slurry include, by mass percentage, 6% of a mixture of nano-alumina and graphite, 8% of a binder, polyvinylidene fluoride, and 86% of an electrolyte.
[0072] Comparative Example 2: The difference between this comparative example and Example 1 is that in the working slurry, the content of lithium niobate is 5%; and in the electrolyte slurry, the porous carbon-coated alumina particles are replaced by a mixture of nano-alumina and graphite, and the mass ratio of nano-alumina to graphite is 5:2.
[0073] Specifically, the components of the active slurry, calculated by mass percentage, include 5% lithium niobate, 16.5% nano-aluminum oxide, 4% polyvinylidene fluoride as a binder, and 74.5% N-methylpyrrolidone as a solvent.
[0074] The components of the electrolyte slurry include, by mass percentage, 6% of a mixture of nano-alumina and graphite, 8% of a binder, polyvinylidene fluoride, and 86% of an electrolyte.
[0075] Comparative Example 3: The difference between this comparative example and Example 1 is that the content of lithium niobate in the working slurry is 5%.
[0076] Specifically, the components of the active slurry, calculated by mass percentage, include 5% lithium niobate, 16.5% nano-aluminum oxide, 4% polyvinylidene fluoride as a binder, and 74.5% N-methylpyrrolidone as a solvent.
[0077] Comparative Example 4: The difference between this comparative example and Example 1 is that in the working slurry, the content of lithium niobate is 10%; and in the electrolyte slurry, the porous carbon-coated alumina particles are replaced by a mixture of nano-alumina and graphite, and the mass ratio of nano-alumina to graphite is 5:2.
[0078] Specifically, the components of the active slurry, by mass percentage, include 10% lithium niobate, 11.5% nano-aluminum oxide, 4% polyvinylidene fluoride as a binder, and 74.5% N-methylpyrrolidone as a solvent.
[0079] The components of the electrolyte slurry include, by mass percentage, 6% of a mixture of nano-alumina and graphite, 8% of a binder, polyvinylidene fluoride, and 86% of an electrolyte.
[0080] Comparative Example 5: The difference between this comparative example and Example 1 is that the content of lithium niobate in the working slurry is 10%.
[0081] Specifically, the components of the active slurry, by mass percentage, include 10% lithium niobate, 11.5% nano-aluminum oxide, 4% polyvinylidene fluoride as a binder, and 74.5% N-methylpyrrolidone as a solvent.
[0082] Comparative Example 6: The difference between this comparative example and Example 1 is that in the electrolyte slurry, the porous carbon-coated alumina particles are replaced by a mixture of nano-alumina and graphite, and the mass ratio of nano-alumina to graphite is 5:2.
[0083] Specifically, the components of the electrolyte slurry include, by mass percentage, 6% of a mixture of nano-alumina and graphite, 8% of a binder, polyvinylidene fluoride, and 86% of an electrolyte.
[0084] Test example: Test object: Batteries were prepared according to Examples 1 to 5 and Comparative Examples 1 to 6.
[0085] Test item: Cycle life - the number of cycles of 0.5C charge / 0.5C discharge until the capacity retention rate drops to 80%.
[0086] Test results: See Table 1.
[0087] Table 1. Test data of the experimental example
[0088]
[0089]
[0090] Result analysis: Analyze Example 1-Example 5 and combine the data in Table 1 and Figure 1 It can be seen that the battery prepared by the present invention has a cycle number of more than 1691 times at 0.5C charge / 0.5C discharge until the capacity retention rate decreases to 80%.
[0091] Analyze Example 1 and Comparative Examples 1-6 and combine the data in Table 1 and Figure 1 By comparing Comparative Example 1 and Comparative Example 2, compared with Comparative Example 1, the working slurry of Comparative Example 2 contains 5% lithium niobate, and the cycle life of the battery obtained is 1518 times, which is significantly greater than the cycle life of the battery obtained in Comparative Example 1 of 1469 times, indicating that adding 5% lithium niobate to the working slurry can increase the cycle life of the battery obtained.
[0092] By comparing Comparative Example 2 and Comparative Example 3, compared with Comparative Example 2, the electrolyte slurry of Comparative Example 3 contains porous carbon-coated alumina particles. As a result, the cycle life of the battery obtained is 1525 times, which is very close to the cycle life of 1518 times of the battery obtained in Comparative Example 2, indicating that when the working slurry contains 5% lithium niobate, the presence of porous carbon-coated alumina particles in the electrolyte slurry has no obvious effect on the cycle life of the battery.
[0093] By comparing Comparative Example 1 and Comparative Example 4, compared with Comparative Example 1, the working slurry of Comparative Example 4 contains 10% lithium niobate, and the cycle life of the resulting battery is 1624 times, which is significantly greater than the cycle life of the battery obtained in Comparative Example 1 of 1469 times, and significantly greater than the cycle life of the battery obtained in Comparative Example 2 of 1518 times, indicating that increasing the content of lithium niobate in the working slurry from 5% to 10% can further increase the cycle life of the resulting battery.
[0094] By comparing Comparative Example 4 and Comparative Example 5, compared with Comparative Example 4, the electrolyte slurry of Comparative Example 5 contains porous carbon-coated alumina particles, and the cycle life of the battery obtained is 1671 times, which is greater than the cycle life of 1624 times of the battery obtained in Comparative Example 4, indicating that when the working slurry contains 10% lithium niobate, the electrolyte slurry containing porous carbon-coated alumina particles can slightly increase the cycle life of the battery.
[0095] Comparing Comparative Example 1 and Comparative Example 6, compared with Comparative Example 1, the slurry of Comparative Example 6 contains 16% lithium niobate, and the cycle life of the battery obtained is 1598 times, which is significantly greater than the cycle life of the battery obtained in Comparative Example 1, which is 1469 times; however, it is less than the cycle life of the battery obtained in Comparative Example 4, which is 1624 times, indicating that the increase of the content of lithium niobate in the slurry from 10% to 16% will lead to a decrease in the cycle life of the obtained battery. This is because the content of lithium niobate is too high, the repulsion effect on lithium ions is too strong, and the distribution and reverse migration of lithium ions are too greatly affected, which has a negative effect.
[0096] By comparing Comparative Example 6 and Example 1, compared with Comparative Example 6, the electrolyte slurry of Example 1 contains porous carbon-coated alumina particles, and the cycle life of the resulting battery is 1708 times, which is significantly greater than the cycle life of 1598 times of the battery obtained in Comparative Example 6, and is also significantly greater than the cycle life of 1671 times of the battery obtained in Comparative Example 5, indicating that when the working slurry contains 16% lithium niobate, the porous carbon-coated alumina particles contained in the electrolyte slurry can produce a synergistic effect therewith, thereby synergistically improving the cycle life of the obtained battery.
[0097] This is because the traction effect of porous carbon-coated alumina particles on lithium ions will be amplified by the repulsion effect of lithium niobate on lithium ions. Although the repulsion effect of 16% lithium niobate on lithium ions is too strong to a certain extent, which will lead to a reverse effect, at the same time, it can also stimulate the traction effect of porous carbon-coated alumina particles on lithium ions to be more prominent, and then work synergistically to make the final effect better.
[0098] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0099] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a diaphragm-free all-solid-state battery, characterized in that: The steps include: S1. The positive current collector surface is coated with positive electrode slurry, with a surface loading of 25-30 mg / cm 2 , bake to a semi-dry state to obtain a positive electrode sheet; S2, positive electrode surface coating slurry, surface loading 4-5mg / cm 2 , baked to a semi-dry state to form an active layer; the components of the active slurry, calculated by mass percentage, include 15-18% lithium niobate, 5-6% nano-aluminum oxide, 3-5% binder and the remainder solvent; S3, the surface of the active layer is coated with electrolyte slurry, with a surface loading of 15-18 mg / cm 2 , baked to a semi-dry state to form a semi-solid electrolyte; the components of the electrolyte slurry, measured by mass percentage, include 5-7% porous carbon-coated alumina particles, 7-9% binder and the remainder of electrolyte; S4, the surface of the semi-solid electrolyte is coated with negative electrode slurry, with a surface loading of 25-30 mg / cm 2 Then, a negative current collector is placed on the surface and the surface is pressurized to a pressure of 450-650 N / m 2 , heating treatment at 80-100° C. in an oven in an inert environment for 12-15 hours to obtain a battery cell; S5. Encapsulate, compact and seal the battery cell to obtain a diaphragm-free all-solid-state battery.
2. The method for preparing a diaphragm-free all-solid-state battery according to claim 1, characterized in that: In S3, the preparation method of the porous carbon-coated alumina particles is as follows: A1. Disperse 1 part of nano-alumina in 10-15 parts of anhydrous ethanol by weight, add 0.02-0.04 parts of silane coupling agent, stir for 20-30 minutes, filter, and obtain activated alumina; A2, mixing the activated alumina obtained in A1 with oleic acid in a mass ratio of 1:3, and ball milling for 0.5-1.5 h, filtering, and obtaining modified alumina; A3. Add modified alumina, fine-grained asphalt and graphite in a mass ratio of 5:1:1 into a high-speed mixer, stir for 2-3 hours, mix evenly, and obtain a mixture; A4. Place the mixture in a tube furnace, and under nitrogen protection, heat it to 1000-1200°C at 3-5°C / min, keep it warm for 4-6 hours, and then naturally cool it to room temperature. Grind it, and pass it through a 500-mesh screen to obtain porous carbon-coated alumina particles.
3. The method for preparing a diaphragm-free all-solid-state battery according to claim 2, characterized in that: In A1, the silane coupling agent is KH550.
4. The method for preparing a diaphragm-free all-solid-state battery according to claim 1, characterized in that: In S3, the electrolyte is lithium manganese iron phosphate electrolyte KLD-LMFP03A.
5. The method for preparing a diaphragm-free all-solid-state battery according to claim 1, characterized in that: In S1, the components of the positive electrode slurry include, by mass percentage, 45-50% lithium cobalt oxide, 4-5% binder, 2-3% carbon black and the remainder solvent.
6. The method for preparing a diaphragm-free all-solid-state battery according to claim 1, characterized in that: In S4, the components of the negative electrode slurry include, by mass percentage, 35-40% silicon carbon, 4-5% binder, 2-3% carbon black and the remainder solvent.
7. The method for preparing a diaphragm-free all-solid-state battery according to any one of claims 1 to 6, characterized in that: The binder includes polyvinylidene fluoride and / or sodium carboxymethyl cellulose.
8. The method for preparing a diaphragm-free all-solid-state battery according to any one of claims 1 to 6, characterized in that: The solvent includes N-methylpyrrolidone and / or ethyl methyl carbonate. The method for preparing a diaphragm-free all-solid-state battery according to any one of claims 1 to 6, characterized in that: The positive current collector is aluminum foil, and the negative current collector is copper foil.
Citation Information
Patent Citations
Processing method for improving beta-alumina solid electrolyte ceramic surface sodium wettability
CN103094629A
Method for preparing aluminum oxide / carbon aerogel composite material
CN104741046A
Solid electrolyte structure, preparation method thereof and lithium battery
CN108155410A
Multi-layer structured composite electrolyte and secondary battery using same
CN110495037A
Carbon-coated aluminum oxide ceramic material as well as preparation method and application thereof
CN113698183A
Cited By
A uv-cured positive electrode sheet and a solid-state battery
CN122781820A